2008
DOI: 10.1097/cej.0b013e3282f0c02c
|View full text |Cite
|
Sign up to set email alerts
|

Case–control study of coffee consumption and the risk of endometrial endometrioid adenocarcinoma

Abstract: This study examined the association between coffee consumption and the risk of endometrial endometrioid adenocarcinoma (EEA) in Japan by a case-control design. The cases consisted of 107 women less than 80 years of age from two medical centers who had been histopathologically diagnosed to have EEA. The controls, selected from the participants of a cancer-screening program, were 214 women, with two controls selected for each case (matched for age and for area of residence). A self-administered questionnaire con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
36
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 18 publications
7
36
0
Order By: Relevance
“…Of 8 studies, 4 case-control studies showed an inverse association 15-18 whereas 3 case-control 12-14 and 1 prospective cohort studies found no association. 19 Our results were in agreement with previous case-control studies which reported a decreased risk of endometrial cancer with coffee consumption in Japan, 17,18 Greece 16 and Sweden. 15 All these studies were conducted in countries where the prevalence of HRT use is relatively low, 25 except for that in Sweden.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Of 8 studies, 4 case-control studies showed an inverse association 15-18 whereas 3 case-control 12-14 and 1 prospective cohort studies found no association. 19 Our results were in agreement with previous case-control studies which reported a decreased risk of endometrial cancer with coffee consumption in Japan, 17,18 Greece 16 and Sweden. 15 All these studies were conducted in countries where the prevalence of HRT use is relatively low, 25 except for that in Sweden.…”
Section: Discussionsupporting
confidence: 83%
“…To date, only 1 case-control study has reported an association between coffee consumption and risk of endometrial cancer in postmenopausal women with practically no HRT. 18 The study found that coffee consumption was inversely associated with endometrial cancer in postmenopausal but not in premenopausal women in Japan, 18 where the prevalence of HRT use is low. 24 In our study, although we could not obtain information on menopausal status at diagnosis of endometrial cancer, 79% of cases in premenopausal women at baseline were aged 50 years or older at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The details of the design and setting of this study have already been described [15]. Briefly, we defined cases as women who met the following criteria: (1) those who were diagnosed as having endometrial cancer and underwent total hysterectomy at either Tohoku University Hospital between November 2002 and the end of March 2007 or Miyagi Cancer Center between June 2005 and the end of June 2006; (2) those under 80 years of age and residents of Miyagi Prefecture, Japan; (3) those whose cancer was histopathologically diagnosed as EEA; and (4) those with no history of cancer at any other organ or site.…”
Section: Methodsmentioning
confidence: 99%